Lightning protection on photovoltaic systems: A review on current and recommended practices. (February 2018) - Ahmad, N.I.; Ab-Kadir, M.Z.A.; Izadi, M.; Azis, N.; Radzi, M.A.M.; Zaini, N.H.; Nasir, M.S.M.
Abstract: In many countries, solar photovoltaic (PV) systems are regarded as one of the best renewable energy (RE) sources in terms of cost of installation, return of investment (ROI), incentive and benefit to the end users. PV systems are always installed on the rooftop or outdoor locations, which give high possibility of getting struck by the lightning. Consequently, this would affect the level of power generated as well as economic issues, which should be borne in mind by the developers and the systems' owners. In order to avoid faults and equipment's damages that lead to severe effects, the lightning protection in PV installations is very important and practically needed. Therefore, determination of the necessity for lightning protection and the risk connected to lightning is obliged to be evaluated as it is the essential ways in adopting the correct protective measures for the systems. This paper identifies the fundamental aspects of lightning interaction on PV and to summarize the lightning protection system requirement according to the standards and guidelines. The necessities of lightning protection on the PV systems and its barrier, the need for different lightning protection system on PV systems as well as its recommended practices are also discussed in this paper.